Isolation, Preliminary Structural Insights, Characterization, and Antioxidant Potential of a New High-Molecular Weight Complex Phenolic Polymer Developed from Olive Mill Wastewater - Antonio Lama-Muñoz; Alejandra Bermúdez-Oria; Fátima Rubio-Senent; Guillermo Rodríguez-Gutiérrez; África Fernández-Prior; Juan Fernández-Bolaños (Antioxidants)
Olive mill wastewater (OMW), a byproduct of the olive oil industry, is a potential source of natural bioactive phenolic polymers. In this work, a column chromatography technique was used for the isolation of a new complex polymer (named OMW-2000XAD) from OMW via fractionation on Amberlite® XAD16 resin. The developed procedure was simple and proved to be reproducible using OMW from two different sources. OMW-2000XAD was further characterized by elemental, glycosidic, and amino acid composition analysis, as well as spectroscopic techniques. The polymer’s molecular size, which was estimated via gel filtration chromatography, was 1960 kDa, which is significantly larger than other high-molecular weight fractions previously isolated from OMW or other agro-industrial wastes. OMW-2000XAD was mainly composed of phenolic compounds (89.8%). It also contained polysaccharides (16.1%) and proteins (10.3%), with glucose (12.25%) and cysteine (1.71%) being the most abundant sugar and amino acid, respectively, as well as metals (1.29%, primarily potassium). However, due to its low solubility, complexity, and heterogeneous composition, it was not possible to identify all phenolic compounds or elucidate a definitive structure via MS, FTIR, and NMR. OMW-2000XAD exhibited strong radical scavenging antioxidant capacity (ABTS•+, DPPH• and peroxyl radicals), with results up to 7415 µmol Trolox equivalent/mol (ORAC method), but showed no antiproliferative effects, highlighting the need for further research.